Irrigation by conjunctive use of surface water and ground water (case study : Mahanadi-Kathjori-Devi Delta, India) - Misra, Debasmita; Gupta, Ashim Das; Bogardi, Janos J.; Nielsen, Steen Asger; France (Bangkok : Asian Institute of Technology, 1986)
This study is an attempt towards the formulation of an optimization model for agricultural planning and management of Mahanadi-Kathjori-Devi delta system. The study involves the following aspects: (a) The study of the physical system and its socio-economic boundaries. (b) Study of the hydrologic processes of the system. (c) Estimating the parameters for the management of the system. (d) Formulating a chance constrained optimization model with streamf low as a chance occurence. (e) Testing the model to the real life data of the system. (f) Conducting sensitivity analysis and suggesting alternate management plans. Linear prograrrming is used to solve the model for maximization of net return from the study area. However, this study is a first attempt towards the formulation of a scientific based decision making model to facilitate decision support to the various agencies for this particular system. The study suggests that groundwater is not required for irrigation purposes at 95% confidence level of streamflow. The terms confidence level and reliability level are alternately used in order to define a probability of occurrence of the event as has been used by Maji and Heady (1978) . The net return can be maximized with proper management of the resources. The sensitivity of the model to different changes represents real life situation. The system has a great capability of utilizing the available water resources. A 20% variation in input costs do not affect the optimal agricultural planning. The system is capable to handle critical dry periods with low precipitation and surface water availability.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Irrigation -- India